Investigation of the Reproducibility of Portable Optical Coherence Tomography in Diabetic Macular Edema - Yoshiaki Chiku; Takao Hirano; Marie Nakamura; Yoshiaki Takahashi; Hideki Miyasaka; Ken Hoshiyama; Toshinori Murata (MDPI AG, 2024)
Background: Diabetic macular edema (DME) causes vision impairment and significant vision loss. Portable optical coherence tomography (OCT) has the potential to enhance the accessibility and frequency of DME screening, facilitating early diagnosis and continuous monitoring. This study aimed to evaluate the reliability of a portable OCT device (ACT100) in assessing DME compared with a traditional stationary OCT device (Cirrus 5000 HD-OCT plus). Methods: This prospective clinical investigation included 40 eyes of 33 patients with DME. Participants with significant refractive errors (myopia > −6.0 diopters or hyperopia > +3.0 diopters), vitreous hemorrhage, tractional retinal detachment, or other ocular diseases affecting imaging were excluded. Spectral-domain OCT was performed by a single examiner using both devices to capture macular volume scans under mydriasis. Central macular thickness (CMT) was evaluated using the analysis software for each device: Cirrus used version 6.0.4, and ACT100 used version V20. We analyzed inter-evaluator and inter-instrument agreements for qualitative assessments of the intraretinal fluid (IRF), subretinal fluid (SRF), and epiretinal membrane (ERM) using Cohen's kappa coefficient, whereas quantitative CMT assessments were correlated using Spearman's correlation coefficient. Results: Substantial inter-evaluator agreement for IRF/SRF (κ = 0.801) and ERM (κ = 0.688) with ACT100 and inter-instrument agreement (κ = 0.756 for IRF/SRF, κ = 0.684 for ERM) were observed. CMT values measured using ACT100 were on average 29.6 μm lower than that of Cirrus (285.8 ± 56.6 vs. 315.4 ± 84.7 μm, p < 0.0001) but showed a strong correlation (R = 0.76, p < 0.0001). Conclusions: ACT100 portable OCT demonstrated high reliability for DME evaluations, comparable to that of stationary systems.